Extended class of exact twistons and crystalline polyethylene - Dutra, Alvaro de Souza [UNESP]; dos Santos, J. R. [UNESP]; Winter, O. C. [UNESP] (Iop Publishing Ltd, 2010)
In this work we study a model used to analyze exact topological twistons in polyethylene. It is observed that an infinite degeneracy in the topological Bolgomol'nyi-Prasad-Sommerfield energy is present in the model. That is a consequence of the structure of the vacuum of the model. Particularly, it is shown that there is no need to restrict the model parameters, as supposed originally. However, since in the PE there is no degeneracy and, furthermore, such degeneracy could completely destroy the chain structure, we perform a perturbation in the model in order to avoid that degeneracy. It is shown that the obtained energy is still in the experimentally allowed range of twiston energy.